Evaluating Clinical Pathway Typhoid Fever Monitoring at ABC Hospital Malang - Ika Shanti Rosalina; Muhammad Mansur; M. Kuntadi Syamsul Hidayat; Kurnia Widyaningrum (Universitas Muhammadiyah Yogyakarta, 2018)
ABC Hospital has implemented 15 Clinical Pathway, and Typhoid Fever is the most cases that can be served. The inaccuracy of the monitoring report on the implementation of Clinical Pathway has prevented the hospital from taking appropriate actions to improve the implementation of Clinical Pathway Typhoid Fever. This study aims to determine the obstacles of monitoring implementation of Clinical Pathway Typhoid Fever in ABC Hospital. This research is a case study and descriptive-explorative research, using document review, field observation, interview, and questionnaire for data collection. The research was conducted in the in-patient wards and medical records room of ABC Hospital during September 2017. The respondents of the research include room physicians, head of inpatient rooms, pediatric, internist, pharmacist, nutritionist, and medical record staff. The result show that factors which impeded implementation of Clinical Pathway monitoring in ABC Hospital were the absence of Clinical Pathway team, the incompatibility of the Clinical Pathway Guide content, the absence of SOP of Clinical Pathway filling form, and the lack of socialization. Suggestion for improving monitoring of Clinical Pathway Typhoid Fever are establish a Clinical Pathway team, revise the Guidance of Clinical Pathway, compile SOP of Clinical Pathway filling form, and do socialization.